Love-Based Curriculum For The Study of Arbain Nawawi Hadith Number 13, 17, 31 - Asmara Windu Azkia; Abdul Rosyad (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
The rapid development of technology and globalization has contributed to the decline of empathy, love, and compassion in social life, including attitudes toward fellow human beings, animals, and the environment. This condition indicates that contemporary educational challenges are not limited to cognitive aspects but also involve a crisis of humanistic and ecological values. This study aims to examine the values of love and compassion contained in Hadith Al-Arba'in An-Nawawiyyah numbers 13, 17, and 31, and to analyze their relevance to the substance of the Love-Based Curriculum (KBC). This research employs a qualitative descriptive approach using library research methods, with Al-Arba'in An-Nawawiyyah by Imam An-Nawawi as the primary source. The findings reveal that these hadiths emphasize love for fellow human beings, compassion toward animals, concern for the natural environment (kauniyah values), and self-restraint from excessive attachment to worldly matters. These values are closely aligned with the substance and objectives of the Love-Based Curriculum, which positions love and compassion as the foundation of the educational process. Thus, the Love-Based Curriculum can be understood as an educational approach that integrates love, empathy, and socio-ecological awareness, whereby Islamic character education emerges as an implication of the internalization of these values. Hadith Al-Arba'in An-Nawawiyyah, particularly numbers 13, 17, and 31, is therefore relevant as a normative reference for developing humanistic, ethical, and sustainable education.